2020
DOI: 10.5867/medwave.2020.10.8064
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and epidemiological characterization of patients with psoriasis and the prescription of biological therapy in Venezuela: a cross-sectional study

Abstract: Introduction Psoriasis is a chronic disease that affects the skin. One hundred twenty-five million people around the world suffer from this condition. In specific groups of patients, the joints may also be involved. To control and follow-up patients with psoriasis, psoriasis area severity and dermatological quality of life measurements were established. Both parameters are necessary for the initiation of biological therapy, as specified in the psoriasis management guide (2015) of the national committee of rheu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Studies from Venezuela 18 and Argentina 19 have reported similar rates of LTBI among Pso patients (10.4% and 16%, respectively). In Colombia, 20 the prevalence was significantly higher at 99%.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Studies from Venezuela 18 and Argentina 19 have reported similar rates of LTBI among Pso patients (10.4% and 16%, respectively). In Colombia, 20 the prevalence was significantly higher at 99%.…”
Section: Discussionmentioning
confidence: 85%
“… Was appropriate statistical analysis used? Descriptive cross-sectional studies Rada JR, et al 18 Figueroa P, et al 19 Úsuga F, et al 14 Lopes N, et al 6 Lopes LC, et al 17 Silveira MSN, et al 33 Gonçalves LMT, et al 21 Lopes N, et al 16 Was the sample frame appropriate to address the target population? Were study participants sampled in an appropriate way?…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation